Effect of trace rare earth element Er on Al-Zn-Mg alloy - 徐国富 牟申周 杨军军 金头男 聂祚仁 尹志民 (Transactions of Nonferrous Metals Society of China, 2006)
Al-6Zn-2Mg and Al-6Zn-2Mg-0.4Er alloys were prepared by cast metallurgy. The effects of trace Er on the mechanical properties, recrystallization behavior and age-hardening characteristic of Al-Zn-Mg alloy were studied. The effect of Er on microstructures was also studied by OM, XRD, SEM, EDS and TEM. The results show that the addition of Er on Al-6Zn-2Mg alloy is capable of refining grains obviously. The addition of Er can improve the strength considerably by strengthening mechanisms of precipitation and grain refinement. With the addition of Er into Al-6Zn-2Mg alloy, the aging process is quickened and the age-hardening effect is heightened. Er additive can retard the recrystallizing behavior of Al-6Zn-2Mg alloy and cause the increase of recrystallization temperature due to the pinning effect of fine dispersed Al3Er precipitates on dislocations and subgrain boundaries.